Intussusception- A Case Report - Gurubacharya, SM; Gurubacharya, RL (Journal of Nepal Paediatric Society, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Intussusception, the invagination of a portion of the intestine into itself, is one of the emergencies in infancy and childhood. The etiology may be idiopathic or secondary to some pathology within the wall of the bowel. Most cases (90%) are idiopathic with no identifiable lesion acting as the lead point or pathological apex of the intussusceptum Children may present at any age but this occurs most commonly in the first year. The mode of presentation may vary depending upon the time of presentation. A case of intussusception confirmed with the help of an abdominal ultrasound in 10 month old infant who presented with only persistent vomiting but in the absence of classic features is reported with brief review of literature. Key words: vomiting, USG, classic triad doi:10.3126/jnps.v27i2.1586 J. Nepal Paediatr. Soc. Vol.27(2) p.84-86